1995
DOI: 10.1038/375685a0
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of antigen processing by the internal repeat region of the Epstein–Barr virus nuclear antigen-1

Abstract: The Epstein-Barr virus (EBV)-encoded nuclear antigen (EBNA1) is expressed in latently EBV-infected B lymphocytes that persist for life in healthy virus carriers, and is the only viral protein regularly detected in all malignancies associated with EBV. Major histocompatibility complex (MHC) class I-restricted, EBNA1-specific cytotoxic T lymphocyte (CTL) responses have not been demonstrated. Using recombinant vaccinia viruses encoding chimaeric proteins containing an immunodominant human leukocyte antigen A11-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
473
0
5

Year Published

1996
1996
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 736 publications
(489 citation statements)
references
References 26 publications
8
473
0
5
Order By: Relevance
“…Unlike the latency III pattern observed in EBV-related lymphoproliferative disorders in patients with immunodeficiency (Hamilton-Dutoit et al, 1993), NK/T-cell lymphomas may minimize the expression of the latency-associated viral antigens which might be targeted by host immune system. EBNA-1 is constantly expressed by EBV-infected cells in any latency pattern, but the host's immune response never occurs against the molecules (Levitskaya et al, 1995). LMP-1 acts as a direct oncogene to transform epithelial cells morphologically (Fahraeus et al, 1990) and prevent B-lymphoma cells from undergoing apoptosis by up-regulating the expression of cellular bcl-2 (Henderson et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Unlike the latency III pattern observed in EBV-related lymphoproliferative disorders in patients with immunodeficiency (Hamilton-Dutoit et al, 1993), NK/T-cell lymphomas may minimize the expression of the latency-associated viral antigens which might be targeted by host immune system. EBNA-1 is constantly expressed by EBV-infected cells in any latency pattern, but the host's immune response never occurs against the molecules (Levitskaya et al, 1995). LMP-1 acts as a direct oncogene to transform epithelial cells morphologically (Fahraeus et al, 1990) and prevent B-lymphoma cells from undergoing apoptosis by up-regulating the expression of cellular bcl-2 (Henderson et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…EBNA-1 is an immunodominant latent target of EBVspecific CD4 1 T cells [19,20]. Although it has been described in the past to escape from recognition by CD8 1 T cells due to Gly/Ala repeated domains preventing proteasome-dependent processing for presentation on MHC class I [21], more recent studies revealed the existence of EBNA-1-specific CD8 1 T cells [15,22,23]. Moreover, detection of anti-EBNA IgG in seropositive individuals suggests need for CD4 help.…”
Section: Introductionmentioning
confidence: 99%
“…CTLs specific for BARF0 were unable to recognize cells expressing the antigen at low levels, 18 EBNA1 is not processed for HLA class I presentation 13 and LMP1 is frequently mutated. 16 Although LMP2B-specific CTLs have been reported, this protein lacks a significant portion of the LMP2A protein that likely contains important CTL epitopes.…”
Section: Discussionmentioning
confidence: 99%
“…EBNA1 is not processed for HLA class I presentation due to an internal glycine-alanine repeat region. 13 LMP1-specific CTL clones are rare in EBV ϩ donors, 14 and very few LMP1 epitopes have been identified. 15 Moreover, LMP1 displays heterogeneity between viral strains, 16 and CTLs raised against B cell (B95-8 prototype) derived LMP1 may not recognize LMP1 tumor variants.…”
mentioning
confidence: 99%